Biochemical Parameters of Female Wistar Rats Fed Shellfish and Cabbage as Potential Nutritive Supplements for Malnutrition - Zakariya, Sadaf; Fernandez , Patricia (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Inability to meet the nutritional requirements causes malnutrition which further leads to various disorders and makes people susceptible to infections. Malnutrition is a serious problem globally and this research was conducted with an aim to understand the nutritive potentials of Shellfish and Cabbage to help deal with malnutrition. Female Wistar rats in post weaning stage were placed in six different groups on the basis of diets provided for a duration of 20 weeks. Investigations for biochemical parameters such as Total Protein, Albumin, enzymes Aspartate aminotransferase (AST), Alanine aminotransferase (ALT), Alkaline phosphatase (ALP), Bilirubin, Creatinine, Blood Urea Nitrogen, Cholesterol and Triglycerides were done to determine the potentials of these food sources as dietary supplements.